ANALYSIS OF NEUROPSYCHOLOGICAL POTENTIAL EXAMINATION RESULT IN PATIENTS WITH CHRONIC LOW BACK PAIN (World Bulletin of Public Health, 2024)
Episodes of back pain occur during life in 50-99% of the population; the peak of prevalence and morbidity is in the working age. The lumbosacral spine is affected up to 60-80%, which is due to the peculiarities of biomechanics and increased load on this spine. Currently, not enough is known about the different trajectories and exact timing of the onset or development of chronic pain. This is in stark contrast to earlier traditional beliefs that back pain will spontaneously decrease over time. Many authors have shown that degenerative changes in the lumbar spine detected by magnetic resonance imaging (MRI) do not correlate with pain intensity and do not predict the neuropathic component of back pain, necessitating the search for new diagnostic approaches to this problem.
Keywords: neuropsychological potential; patients; chronic pain